2020
DOI: 10.7150/ijms.46614
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with death outcome in patients with severe coronavirus disease-19 (COVID-19): a case-control study

Abstract: Rationale: Up to date, the exploration of clinical features in severe COVID-19 patients were mostly from the same center in Wuhan, China. The clinical data in other centers is limited. This study aims to explore the feasible parameters which could be used in clinical practice to predict the prognosis in hospitalized patients with severe coronavirus disease-19 . Methods: In this case-control study, patients with severe COVID-19 in this newly established isolation center on admission between 27 January 2020 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
166
5
15

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(208 citation statements)
references
References 27 publications
22
166
5
15
Order By: Relevance
“…Furthermore, the characteristics of age, gender and oximetry of our G2 patients were similar to those previously reported [9,18], and the way both cohorts were nally built up within a strict home-con nement regional strategy reproduces a real setting whose results might be used as a model in ongoing pandemic waves. Furthermore, we believe that the higher pcHRRS discriminative performance makes bene cial to maintain and expand the RD entry-door role in the long term to be prepared for future COVID-19 waves or other similar pandemics.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, the characteristics of age, gender and oximetry of our G2 patients were similar to those previously reported [9,18], and the way both cohorts were nally built up within a strict home-con nement regional strategy reproduces a real setting whose results might be used as a model in ongoing pandemic waves. Furthermore, we believe that the higher pcHRRS discriminative performance makes bene cial to maintain and expand the RD entry-door role in the long term to be prepared for future COVID-19 waves or other similar pandemics.…”
Section: Discussionsupporting
confidence: 74%
“…Accelerated heart rate indicates the damage of myocardial energy supply, and one of the complications of patients with COVID-19 is acute myocardial injury. Study has shown that in addition to acute respiratory distress syndrome (ARDS), systemic inflammation with cardiac dysfunction is the main cause of death from severe COVID-19 [23] . So early detection of changes in heart rate and prevention of complications can decrease the mortality of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, 119 articles were excluded by the titles and abstracts, and 43 of the remaining 56 articles were deleted for various reasons, and we were left with 13 articles. According to the literature quality evaluation, 12 articles of 3493 patients [16][17][18][19][20][21][22][23][24][25][26][27][28] were ultimately selected for the meta-analysis ( Figure 1). All these selected studies were published in 2020 with varying sample sizes ranging from 20 to 7614 patients.…”
Section: Research Selection and Quality Assessmentmentioning
confidence: 99%
“…The search strategy identified 7,385 records: 6,528 from PubMed, 465 from CNKI, 322 from Wangfan, and 70 from other sources (Figure 1). After excluding duplicated and irrelevant records, 16 studies were included in this meta-analysis with a total of 10,624 COVID-19 cases ( Table 1) (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Thirteen studies derived from China, while one study came from the USA, one from Spain and one from India.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%